The Marine Scientific Research Legislation and the Principles to Be Subject to Foreigners in the Subjects of Sea Creatures, Their Environment and Their Protection in Turkey Seas: Threats - TanrÄ±verdi, Raziye (Sam Ratulangi University, 2021)
There is a possibility of illegal scientific and strategic research in the Turkey Seas. The comprehensive determination of the principles of marine scientific research in the Turkish Seas will play an important role in terms of national security and national interests.Marine scientific research should be regulated by law in Turkey. With the law to be regulated, diplomatic channels or to which institution to apply depending on the subject of the research, application principles, the report principles after the research, how to follow the way about the sample and material taken, legal procedure principles to be applied in case of not obtaining permission or exiting the scope of the permission, etc. should be explained.